Solve the inequation x^2 - 4x - 12 > 0

4 Answers | Add Yours

hala718's profile pic

hala718 | High School Teacher | (Level 1) Educator Emeritus

Posted on

X^2-4x-12>0

First we will solve the inequality just like we solve any quadric equation.

x^2-4x-12>0

(x-6)(x+2)>0

That means that both terms are either negative or both positive: OR

(x-6)>0 and (x+2)>0

x>6 and x>-2

==> the x belongs to the interval (6, inf)

OR

(x-6)<0 and (x+2)<0

x<6 and x<-2

Then x belongs to the interval (-inf, -2)

From both solution we observe that x belongs to R except for the interval [-2,6]

then x = R-[-2,6]

Top Answer

giorgiana1976's profile pic

giorgiana1976 | College Teacher | (Level 3) Valedictorian

Posted on

First of all, we'll solve the qudratic equation:

x^2 -4x -12 = 0

After that, to find out the roots of the equation, we'll use the quadratic formula:

x1 = [-b + sqrt(b^2 - 4ac)]/2a, where a=1, b=-4, c =-12

x2 = [-b + sqrt(b^2 - 4ac)]/2a,

after calculation

x1=6, x2=-2

After that, following the rule which says that between the two roots, the values of function have the opposite sign of the "a" coefficient, and outside the roots, the values of the function have the same sign with the coefficient "a", we could find the conclusion that inequation is positive on the following intervals:

x belongs to the interval (-infinite, -2) U (6, + infinite).

tonys538's profile pic

tonys538 | Student, Undergraduate | (Level 1) Valedictorian

Posted on

The in-equation x^2 - 4x - 12 > 0 has to be solved.

x^2 - 4x - 12 > 0

x^2 - 6x + 2x - 12 > 0

x(x - 6) + 2(x - 6) > 0

(x + 2)(x - 6) > 0

This is true when either both x + 2 and x - 6 are greater than 0 or when both x + 2 and x - 6 are less than 0

x + 2 > 0 and x - 6 > 0

x > -2 and x > 6

This is true when x > 6

x + 2 < 0 and x - 6 < 0

x < -2 and x < 6

This is true when x < -2

The solution of the given inequation is `(-oo, -2)U(6, oo)`

neela's profile pic

neela | High School Teacher | (Level 3) Valedictorian

Posted on

To solvw x^2-4x-12 = 0.

Solution:

x^2-4x-12 = 0 could be expressed as (x^2-4x+4) -4 -12 = 0. Or

 (x-2)^2 - 16  = 0. Or

(x-2)^2 -4^2 = 0. Or

{(x-2)+4}{(x-2)-4 } = 0. as a^2-b^2 = (a+b)(a-b).

(x+2)(x-6) = 0. Or

x+2 = 0 Or x-6 = 0.

x+2 = 0 gives x=-2. And x-6 = 0 gives, x = 6.

We’ve answered 318,917 questions. We can answer yours, too.

Ask a question